Successful endoscopic closure of gastrocutaneous fistula with an over-the-scope clip - Magalhães, K. (2015)
Submitted by José Pereira (jro.pereira@gmail.com) on 2015-07-28T13:21:05Z No. of bitstreams: 1 successful endoscopic closure.pdf: 942421 bytes, checksum: 9175760a5e97e5c2647991b0057f5a6b (MD5)